Books and Periodicals Received (Review of Economic Studies, 1945)
Books and Periodicals Received The Review of Economic Studies, Volume 13, Issue 2, 1945, Pages 109–110, https://doi.org/10.1093/restud/13.2.109 Published: 01 September 1945